PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TYPE PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR IPAS SISWA KELAS IV C DI SDN 02 MOJOREJO KOTA MADIUN - Ma’rifatul Wakhidah; Ivayuni Listiani; Sayekti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
ABSTRACT The aim of this research is to determine the increase in learning outcomes in science and science subjects for class IV students at SDN 02 Mojorejo, Madiun City through the Picture and Picture learning model. This type of research is Classroom Action Research (PTK). Carried out in two cycles to determine the improvement in student learning outcomes in more detail. The subjects of this research were class IV C students at SDN 02 Mojorejo, Madiun City with a total of 26 students. This research uses two learning cycles where each cycle consists of one meeting with the following learning stages: planning, implementation, observation, and reflection. The data collection techniques are by using interview, observation and test techniques. Meanwhile, data analysis uses qualitative methods by means of data reduction, data presentation, data analysis, and drawing conclusions as well as quantitative-based data analysis by analyzing data through test results. The results of this research are that the use of the picture and picture type cooperative learning model can improve the learning outcomes of class IV C students at SDN 02 Mojorejo, Madiun City. The results of the research after using the picture and picture type cooperative learning model were that in cycle 1 they obtained an average of 68 with a percentage of 57.6% for students whose scores were above average and in cycle 2 they obtained an average of 78 with a presentation of 69.2 % for students whose scores are above average. So the application of the picture and picture type cooperative learning model can improve the learning outcomes of class IV students at SDN 02 Mojorejo, Madiun City. Keywords: picture and picture, learning outcomes, students ABSTRAK Tujuan penelitian ini yaitu untuk mengetahui peningkatan hasil belajar pada mata pelajaran IPAS siswa kelas IV SDN 02 Mojorejo Kota Madiun melalui model pembelajaran Picture and Picture. Jenis penelitian ini yakni Penelitian Tindakan Kelas (PTK). Dilakukan dengan dua kali siklus untuk mengetahui peningkatan hasil belajar siswa lebih detail. Subjek dari penelitian ini yakni siswa kelas IV C SDN 02 Mojorejo Kota Madiun dengan jumlah 26 siswa. Penelitian ini menggunakan dua siklus pembelajaran dimana setiap siklus terdiri dari satu kali pertemuan dengan tahapan pembelajaran sebagai berikut : perencanaan, pelaksanaan, observasi, serta refleksi. Adapun teknik pengumpulan data yakni dengan menggunakan teknik wawancara, observasi, dan tes. Sedangkan untuk analisis data menggunakan metode kualitatif dengan cara reduksi data, penyajian data, analisis data, dan pengambilan kesimpulan serta analisis data berbasis kuantitatif dengan menganalisis data melalui hasil tes. Hasil dari penelitian ini yakni penggunaan model belajar kooperatif learning type picture and picture dapat meningkatkan hasil belajar siswa kelas IV C di SDN 02 Mojorejo Kota Madiun. Hasil penelitian setelah menggunakan model pembelajaran kooperatif learning type picture and picture yakni pada siklus 1 memperoleh rata-rata 68 dengan presentase 57,6% untuk peserta didik yang nilainya diatas rata-rata dan pada siklus 2 memperoleh rata-rata 78 dengan presentasi 69,2% untuk peserta didik yang nilainya diatas rata-rata, maka penerapan model pembelajaran kooperatif learning type picture and picture dapat meningkatkan hasil belajar peserta didik kelas IV di SDN 02 Mojorejo Kota Madiun. Kata Kunci: picture and picture, hasil belajar, siswa